Teachers' Perceptions Regarding the Development of Ecotourism-based Science Teaching Materials - Purwoko, Agus Abhi; Idrus, Agil Al; Harjono, Ahmad; ‎ , Hamidi; Rokhmat, Joni; Sukarso, AA. (KnE Social Sciences, 2024)
Scientific literacy skills can help students solve the everyday-life problems faced in the twenty-first century. This research aims to explore teachers’ perceptions regarding the development of ecotourism-based science teaching materials. The research sample was 21 State Junior School science teachers from across five districts/cities on the island of Lombok. The research instrument is a questionnaire consisting of 10 questions with 4 answer choices (Likert scale), which was adopted from previous research. The collected data were analyzed by finding the percentage of each respondent’s answer. The results showed that 86% of respondents thought that it was necessary to integrate the concept of ecotourism into learning and 83% stated that it was necessary to develop ecotourism-based science teaching materials. Complete results related to the need to improve students’ scientific literacy skills are presented in the article. Keywords: teaching materials, ecotourism, scientific literacy